The Vatican princess [large type] : a novel of Lucrezia Borgia - Gortner, C. W. (Thorndike Press, 2016)
Glamorous and predatory, the Borgias became Italy's most ruthless and powerful family, electrifying and terrorizing their 15th-century Renaissance world. To this day, Lucrezia Borgia is known as one of history's most notorious villainesses, accused of incest and luring men to doom with her arsenal of poison. This novel delves beyond the myth to depict Lucrezia in her own voice, from her pampered childhood in the palaces of Rome to her ill-fated, scandalous arranged marriages and complex relationship with her adored father and her rival brothers -- brutal Juan and enigmatic Cesare.